Research on the Application of NLP-Driven Opinion Sentiment Tendency Analysis in Precision Marketing of New Energy Vehicles - Tang, Na; Daijie, Li; mulang, Bu; Zhongyuan, Liu; Wenjing, Zhu; Chuanxiang, Yang (LPPM STIKI Malang, 2024)
In today's online new media era, online public opinion often influences consumers' purchasing decisions. This dissertation discusses the strategies to promote the development of domestic new energy passenger cars, and combines the comment data of major media platforms, so that enterprises can more accurately understand the public's attitudes and perceptions towards new energy vehicles, and formulate more effective marketing strategies to increase the sales of new energy vehicles. This paper utilizes the nlp sentiment analysis technique, and incorporates 15 original papers to collect nearly 20,000 comments from major websites. It is found that the sales of new energy vehicles continue to rise despite a high proportion of negative online opinions about new energy vehicles, which is closely related to scientific and technological innovations, policy promotion, and consumers' increased acceptance of the concept of green mobility.